Tollip Orchestrates Macrophage Polarization to Alleviate Intestinal Mucosal Inflammation. (3rd February 2022) - Liu, Xiaoming; Ren, Xingxing; Zhou, Lifeng; Liu, Ke; Deng, Liangjun; Qing, Qing; Li, Jin; Zhi, Fachao; Li, Mingsong
Abstract: Background and Aims: Regulation of macrophage polarization is a promising strategy for treating inflammatory bowel disease [IBD]. Tollip is an important negative regulator of Toll-like receptor [TLR]-mediated innate immunity with downregulated expression in the colon tissues of patients with IBD. This study aimed to regulate the expression of Tollip to affect macrophage polarization. Methods: A molecular, targeted immunotherapy method was developed by linking mannose-modified trimethyl chitosan [MTC] with Tollip-expressing plasmids via ionic cross-linking, forming MTC-Tollip nanoparticles with a targeting function. MTC-Tollip selectively targeted mouse intestinal macrophages to regulate the polarization of macrophages for mucosal repair. Results: Orally administered MTC-Tollip significantly elevated Tollip expression in intestinal tissue. Compared with MTC-negative control [NC]-treated mice in which colitis was induced with dextran sodium sulphate [DSS], the MTC-Tollip nanoparticle-treated mice exhibited decreased body weight loss and colon shortening, lower proinflammatory cytokine expression in colon tissues, and greater mucosal barrier integrity. MTC-Tollip treatment decreased TNF-α and iNOS expression but increased CD206 and Arg-1 expression in colon tissue. Tollip overexpression in mouse peritoneal macrophages inhibited lipopolysaccharide [LPS]-induced proinflammatory cytokine production and promoted IL-4-induced M2 expression. The progression of peritoneal macrophages extracted from Tollip −/− mice confirmed the effect of Tollip on macrophage polarization. Western blots showed that Tollip overexpression attenuated the upregulation of TLR pathway-associated targets in M1 macrophages. Conclusions: MTC nanoparticles can be 'intelligent' carriers in immunotherapy. The modulation of Tollip expression in macrophages may be a novel treatment approach for IBD.